2013
DOI: 10.1164/rccm.201212-2318oc
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-controlled Study of Brodalumab, a Human Anti–IL-17 Receptor Monoclonal Antibody, in Moderate to Severe Asthma

Abstract: Inhibition of IL-17 receptor A did not produce a treatment effect in subjects with asthma. The results of the high-reversibility subgroup analysis are of uncertain significance, requiring further study of brodalumab in this asthma subpopulation. Clinical trial registered with www.clinicaltrials.gov (NCT01199289).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
318
3
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(334 citation statements)
references
References 22 publications
4
318
3
9
Order By: Relevance
“…In further support of conducting new studies, an anticipated increase in local infections was observed in the clinical trial by BUSSE et al [80], and this side-effect is in need of further evaluation prior to developing this new pharmacotherapeutic principle.…”
Section: Clinical Trials On the Inhibition Of Il-17 Signalling In Asthmamentioning
confidence: 98%
See 2 more Smart Citations
“…In further support of conducting new studies, an anticipated increase in local infections was observed in the clinical trial by BUSSE et al [80], and this side-effect is in need of further evaluation prior to developing this new pharmacotherapeutic principle.…”
Section: Clinical Trials On the Inhibition Of Il-17 Signalling In Asthmamentioning
confidence: 98%
“…BUSSE et al [80] recently published a report of a clinical trial of an IL-17RA monoclonal antibody in patients with various types of asthma. Interestingly, a beneficial clinical effect was claimed for patients with inadequately controlled asthma who displayed high reversibility in response to a bronchodilator.…”
Section: Clinical Trials On the Inhibition Of Il-17 Signalling In Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, a number of attempts to neutralize the activity of these factors with antibodies like canakinumab, brodalumab [17], adalimumab, golimumab [18], and infliximab did not produce convincing results in clinical trials [19]. None of these agents reduced inflammatory cell counts or produced significant improvements of the clinical outcomes, but raised serious concerns over the safety of TNF-α-blockade and an increased susceptibility to respiratory infections.…”
mentioning
confidence: 99%
“…Although many T-cell populations contribute to the spectrum of allergic asthma phenotypes (2), cytokine-secreting T-helper 2 (T H 2) cells have the capacity to induce allergen-specific IgE (atopy) and invoke many of the pathophysiological manifestations associated with asthma, including airway eosinophilia, mucus hypersecretion, airway remodeling, and airway hyperreactivity. Targeting specific cytokinesignaling pathways in allergic asthma has had mixed efficacy (3)(4)(5), suggesting that additional targets and more focused approaches should be considered (6). Several T H 2 cell lineage-promoting transcriptional regulators, including GATA binding protein 3 (GATA-3) (7), , , and avian musculoaponeurotic fibrosarcoma (cMAF) (10), have been identified in T H 2 cells; however, it is unclear whether other transcriptional regulators are required for T H 2 cell-mediated responses.…”
mentioning
confidence: 99%